A new polychelidan lobster preserved with its eggs in a 165 Ma nodule - Jauvion, Clément (Sci Rep, 2020)
Crustacean eggs are rare in the fossil record. Here we report the exquisite preservation of a fossil polychelidan embedded within an unbroken nodule from the Middle Jurassic La Voulte-sur-Rhône Lagerstätte (France) and found with hundreds of eggs attached to the pleon. This specimen belongs to a new species, Palaeopolycheles nantosueltae sp. nov. and offers unique clues to discuss the evolution of brooding behaviour in polychelidan lobsters. In contrast to their development, which now relies on a long-lived planktic larval stage that probably did not exist in the early evolutionary steps of the group, the brood size of polychelidan lobsters seems to have remained unchanged and comparatively small since the Jurassic. This finding is at odds with reproductive strategies in other lobster groups, in which a long-lived planktic larval stage is associated with a large brood size.